2020
DOI: 10.1002/jbmr.4207
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblasts/Osteocytes sirtuin6 Is Vital to Preventing Ischemic Osteonecrosis Through Targeting VDR-RANKL Signaling

Abstract: Ischemic osteonecrosis (ION) can produce permanent deformity and osteoarthritis in the femoral head and other joints. No biologic treatment has been established, and the molecular mechanisms involved in the pathogenesis of ION have not been elucidated. In this work, we found that treatment with sirtuin6 (Sirt6) suppressed inflammatory cytokines, bone resorption, progression of osteoarthritis, and reduced bone deformity in an ION mouse model. We used a deacetylase mutant adenovirus to confirm that those effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…The TRIzol reagent was used to extract total RNAs from the tissues and cells as previously described [ 22 ]. According to the instructions, 1000 ng of total RNA was reversed and recorded into cDNAs.…”
Section: Methodsmentioning
confidence: 99%
“…The TRIzol reagent was used to extract total RNAs from the tissues and cells as previously described [ 22 ]. According to the instructions, 1000 ng of total RNA was reversed and recorded into cDNAs.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, the effect of SIRT6 on GIONFH in rats was evaluated by micro-CT and histopathology and found that SIRT6 significantly improved the bone mass of the femoral head in glucocorticoid-induced rats, increased the number of trabecular, and decreased the separation of trabecular. New studies have found that Sirt6 Tg mice are resistant to the release of inflammatory factors and the progression of osteocyte death, bone resorption, and osteoarthritis after ischemic surgery, while osteoblast/osteocyte-specific SIRT6 knockout mice show severe bone loss and deformity [ 17 ]. SIRT6 could improve the viability of MC3T3-E1 cells in a femoral head necrosis model induced by hypoxia in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…HBYY001; hopebio) with the aim of simulating the ischaemic-hypoxic microenvironment of vascular injury during SONFH in vitro. The anaerobic capsules in the sealed jars will rapidly absorb atmospheric oxygen and produce CO 2 , eventually bringing the oxygen concentration to less than 1% within 30 min [14].…”
Section: Methodsmentioning
confidence: 99%